Manejo da palha residual de arroz irrigado por inundação, crescimento e produtividade de grãos no ano seguinte - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Rice is a crop of economic and food significance that reaches higher grain yield under irrigated conditions. However, the amount of rice straw remaining can influence the rice grain yield. This work evaluates the influence of residual flooded rice straw on rice growth and grain yield in the following year. The experimental design was completely randomized, whit factorial scheme 5 x 4 x 2, with 4 replications. Five doses of straw (0, 5, 10, 20 and 40 t ha-¹), four application times (3, 2, 1 and 0 months before sowing) and two management forms (surface and incorporated). Irrigated rice cultivar Irga 424 was used and at harvest were determined the number of panicles, shoot dry mass, 100 grain mass and grain yield per pot. Doses of rice straw remaining, application times and surface or incorporated into the soil management influences rice grain yield. Only when there is a high dose of remaining rice straw (40 t ha-¹) greater dry mass of shoots occurs when the straw is applied at sowing. Grain yield is higher when applying the higher dose of straw, with the lower doses the time of application of straw does not alter yield. The maximum rice grain yield is obtained at a dose of 37.3 t ha-¹ of straw remaining in the incorporate management and at 32.7 t ha-¹ in surface straw, in soil with 1.6% organic matter.
Keywords: Oryza sativa; Restos culturais; Manejo do solo; Matéria orgânica; Crop residues; Soil management; Organic matter; CNPQ::CIENCIAS AGRARIAS